Optimizing current standard of care therapy for stage III non-small cell lung cancer - Verma, Vivek (Transl Lung Cancer Res, 2020)
The management of stage III non-small cell lung cancer (NSCLC) remains complex and controversial, with a myriad of potentially feasible options. Given the diversity of non-surgical as well as surgical options, along with recent randomized data regarding adjuvant immunotherapy that has re-defined the standard of care for unresected stage III NSCLC cases, the goal of this narrative review was to provide a contemporary view at how management of these patients can be further optimized. Topics discussed include the following items: optimizing toxicity mitigation strategies (in order to avoid impaired receipt of subsequent therapies), the importance of multidisciplinary tumor boards (MTBs) and multidisciplinary clinics (MDCs), adhering to treatment approaches endorsed by national guidelines, prudently selecting patients for surgical intervention (as compared to non-operative approaches), coordination of multidisciplinary care so as to best preserve all potential therapeutic options, and addressing challenges regarding disparities in access to oncologic care. This review places particular emphasis for community and/or rural centers, which may not have the same level of resources and/or personnel as larger academic institutions. Taken together, these strategies are aimed towards the overarching goal of streamlining oncologic care for stage III NSCLC cases in light of the numerous approaches that currently exist for these patients.